simplify
n-2 = 10n/2 + 4/2
n-2 = 5n + 2
subtract 5n to both sides
n - 2 - 5n = 5n + 2 - 5n
simplify
-4n - 2 = 2
add 2 to both sides
-4n - 2 + 2 = 2 + 2
simplify
-4n = 4
divide both sides by -4
-4n/-4 = 4/-4
simplify
n = -1
hope it helps
Answer:
prob 27
Step-by-step explanation:
Answer:
Step-by-step explanation:
Solution by substitution method
3x+5y=7
and 4x-y=5
Suppose,
3x+5y=7→(1)
and 4x-y=5→(2)
Taking equation (2), we have
4x-y=5
⇒y=4x-5→(3)
Putting y=4x-5 in equation (1), we get
3x+5y=7
⇒3x+5(4x-5)=7
⇒3x+20x-25=7
⇒23x-25=7
⇒23x=7+25
⇒23x=32
⇒x=32/23
→(4)
Now, Putting x=32/23
in equation (3), we get
y=4x-5
⇒y=4(32/23)-5
⇒y=(128-115)/23
⇒y=13/23
∴y=13/23 and x=32/23
Answer:
y = 6
Step-by-step explanation:
Its going by 6's